2009
DOI: 10.4310/atmp.2009.v13.n5.a6
|View full text |Cite
|
Sign up to set email alerts
|

Topological T-duality and T-folds

Abstract: We explicitly construct the C * −algebras arising in the formalism of Topological T-duality due to Mathai and Rosenberg from string-theoretic data in several key examples. We construct a continuous-trace algebra with an action of R d unique up to exterior equivalence from the data of a smooth T d -equivariant gerbe on a trivial bundle X = W × T d . We argue that the 'noncommutative T-duals' of Mathai and Rosenberg [7], should be identified with the nongeometric backgrounds well-known in string theory. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…This suggests that T-duality and doubled geometry is the natural framework to investigate closed string noncommutative geometry. This point was noticed already some time ago for tori with constant B-fields in [60,61], while noncommutative correspondence spaces associated to T-folds are described in [16,13] in the context of open strings. In [63] this was demonstrated by applying T-duality along one direction of a twisted three-torus with non-vanishing geometric flux, which reveals that there is a non-trivial commutation relation between the coordinates in the doubled geometry that is determined by the winding number in the base direction.…”
Section: Introduction and Summary Background And Contextmentioning
confidence: 81%
See 1 more Smart Citation
“…This suggests that T-duality and doubled geometry is the natural framework to investigate closed string noncommutative geometry. This point was noticed already some time ago for tori with constant B-fields in [60,61], while noncommutative correspondence spaces associated to T-folds are described in [16,13] in the context of open strings. In [63] this was demonstrated by applying T-duality along one direction of a twisted three-torus with non-vanishing geometric flux, which reveals that there is a non-trivial commutation relation between the coordinates in the doubled geometry that is determined by the winding number in the base direction.…”
Section: Introduction and Summary Background And Contextmentioning
confidence: 81%
“…However, T-dualising along two cycles gives rise to a space with non-geometric Q-flux whereby one of the cycles is only periodic up to T-duality, which mixes momentum and winding modes; the resulting geometry is thus only well-defined locally and is called a T-fold. An approach to describing these backgrounds mathematically in the context of open string theory was put forward in [66,28,32,13] using the language of noncommutative geometry:…”
Section: Introduction and Summary Background And Contextmentioning
confidence: 99%
“…In contrast to these analyses, here we work in a controlled setting with (doubled) twisted tori and quantised fluxes, without any linear approximations and with an exact effective field theory description of the string geometry. Noncommutative and nonassociative geometries were suggested as global (algebraic) descriptions of T-fold and R-flux non-geometries respectively in the mathematical framework of topological T-duality in [46][47][48][49], which strictly speaking only applies to the worldvolumes of D-branes, but it was further suggested that such a description should also apply to the closed string background itself. Such a suggestion requires further clarification, insofar that in closed string theory itself there is no immediate evidence for such nonassociative structures.…”
Section: Introductionmentioning
confidence: 99%
“…Such a description is provided by generalized geometry [17,18,19,20,21]. In some situations, as encountered for example in T-fold backgrounds [22,23,24,25,26], it is even more elegant to use an anti-symmetric bi-vector together with a metric to describe T-dual backgrounds. An immediate question is about the geometric analogues e.g.…”
Section: Mathematical Backgroundmentioning
confidence: 99%